Theorizing the Impact of Targeted Narratives: Model Admiration and Narrative Memorability. Issue 5 (4th May 2017) - Christy, Katheryn R.; Jensen, Jakob D.; Sarapin, Susan H.; Yale, Robert N.; Weaver, Jeremy; Pokharel, Manusheela
Abstract : Communication campaigns often include components that have been designed for a specific population, a strategy referred to as targeting. Targeted narratives are story-based components of a campaign that feature a character or situation relevant to the intended audience. Though commonplace, few studies have explicated the underlying mechanisms by which targeted narratives exert influence. In a message evaluation study, 316 women aged 40–75 ( Mage = 51.19, SD = 8.11) were exposed to one of two targeted narratives and asked to complete measures of model admiration, narrative memorability, and intentions to receive a mammography. Targeting was based upon affiliation with the Mormon church. The results revealed that the relationship between the targeted narratives and screening intentions was especially strong for women from the target population who admired the depicted models and found the stories memorable.